Prediction and Monitoring of Therapeutic Response by Molecular Imaging - Kim, E. E.; Yang, David (Current Medical Imaging, 2010)
Drug response is a fundamental concept that describes the phenomenon in essence whereby some patients benefit from a particular therapy whereas others, despite apparently identical clinical and histopathologic characteristics. Monitoring therapeutic response has been a crucial part of clinical oncology with two approaches. One is to measure markers specifically secreted by tumor cells into the blood, and the other approach uses changes in tumor size. However, their limitations have been well recognized. Intense efforts have been made to understand the mechanisms underlying the therapeutic responsiveness or at least to identify parameters that correlate closely with the response. However, these molecular predictors such as genes are far from perfect as known in breast cancers with HER2 and trastuzumab. Drug actions are related to receptor or enzyme activity, and the current assays are purely morphologic studies. However, imaging with radiolabeled drugs reflects not only the presence or absence but also functioning status of specific receptor or enzyme. Radiolabeled drugs may predict or detect favorable vs unfavorable patients to specific therapy. We have radiolabeled various drugs and agents such as taxol, folate, guanine, metronidazole, annexin, glucosamine, endostatin, antiphosphotyrosine antibody and estradiol, and radiolabled estradiol is specific to predict and monitor hormonal therapy.
Keywords: Apoptosis